Communication and Social Innovation Transfer. Codification and Knowledge Communities - Unceta Satrústegui, Alfonso (Historia y Comunicación Social, 2014)
Successful social innovations require the incorporation of external knowledge as well as the transformation of the knowledge produced during the development of the innovations themselves. In order for this process of communication and transference to be properly conducted it is not sufficient to have the know-how (tacit dimension) but it also necessary to encode different levels of knowledge (explicit dimension). Thus the knowledge management in an innovative community is a process of encoding scattered knowledge, either articulating or assimilating coding systems.